Validity and reliability of ergonauta encoder to assess countermovement jump performance - Gheller, R. G.; Kons, R. L.; Külkamp, W.; Dal Pupo, J.; Detanico, D. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2025)
This study aimed to test the reliability and criterion validity of the Ergonauta encoder to assess countermovement jump (CMJ) performance, considering jump height and mean propulsive velocity metrics. Twenty-three recreationally active men participated in this study. The participants were positioned on a force plate with the Ergonauta individually connected through a belt. Two CMJs were performed, and the jump height and mean propulsive velocity metrics were analyzed. The intraclass correlation coefficient (ICC) and typical error (TE) were used as relative and absolute reliability indicators, respectively. The Pearson correlation was used to verify the relationship between the Ergonauta and force plate derived-metrics, and the Bland-Altman plot was used to verify the agreement between the metrics (Ergonauta encoder and force plate), with the level of significance set at p < 0.05. The results show excellent relative reliability for both metrics, considering the two evaluation devices (ICC = 0.95-0.99, TE = 1.02-2.46). The jump height and mean propulsive velocity obtained by the Ergonauta encoder and the force plate were strongly correlated (r = 0.95; r = 0.90, respectively, p < 0.01). The Bland-Altman plot showed good agreement for both metrics (jump height and mean propulsive power) and equipment (close to 0). We concluded that the Ergonauta encoder is reliable and valid for assessing CMJ performance, particularly the jump height and mean propulsive velocity metrics.